2020
DOI: 10.19173/irrodl.v21i2.4606
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pre-Service Teaching Practice for Online and Distance Education Students in Pakistan

Abstract: In addition to conventional modes, teacher education programs in Pakistan are also offered through online and distance education. Teaching practice is a significant component of pre-service teacher education programs. Assessing the quality of teaching practice for pre-service student teachers is important, as these modules train the prospective teachers for their professional teaching careers. Virtual University of Pakistan (VU), an online university, offers pre-service teacher education programs. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…Misunderstanding often occurs in the problem solving process. This supports the results of the research [15], [16], [18] that misunderstanding always appears in solving student problems. Students may have mastered the material being studied, but have not been able to implement it in solving the problems at hand.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Misunderstanding often occurs in the problem solving process. This supports the results of the research [15], [16], [18] that misunderstanding always appears in solving student problems. Students may have mastered the material being studied, but have not been able to implement it in solving the problems at hand.…”
Section: Resultssupporting
confidence: 91%
“…Students may have mastered the material being studied, but have not been able to implement it in solving the problems at hand. This strengthens the research [18]. This misunderstanding occurs because learning is carried out online so that students cannot face-toface with the lecturer.…”
Section: Resultssupporting
confidence: 58%
“…However, the difference between both types of teaching was very small, due to the aspects highlighted in previous sections. Various studies have shown that if a course is graded in online mode in the same way as in F2F, the online grades are clearly lower [ 66 ]. It is therefore essential that grading methods are adjusted to the type of teaching [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“… Course unit grades were not influenced by the abrupt change in the teaching modality, due to the way that the teachers had adapted the evaluation system. An online course unit that is graded in the same way as a F2F course will usually result in significantly lower grades [ 66 ]. …”
Section: Discussionmentioning
confidence: 99%
“…In usual teaching practice, students go to schools in real settings and perform actual teaching in classrooms. A university supervisor and the cooperating teacher are available for the student-teachers during this teaching practice activity (Abdullah & Mirza, 2020). The students select the schools and perform 6 weeks to 16 weeks teaching practice depending upon the degree programme.…”
Section: Teacher Education Institutionsmentioning
confidence: 99%